Identification of QTLs and critical genes related to sugarcane mosaic disease resistance - Lu, Guilong; Wang, Zhoutao; Pan, Yong-Bao; Wu, Qibin; Cheng, Wei; Xu, Fu; Dai, Shunbin; Li, Boyu; Que, Youxiong; Xu, Liping (Frontiers in Plant Science, 2023)
Mosaic viral diseases affect sugarcane productivity worldwide. Mining disease resistance-associated molecular markers or genes is a key component of disease resistance breeding programs. In the present study, 285 F1 progeny were produced from a cross between Yuetang 93-159, a moderately resistant variety, and ROC22, a highly susceptible variety. Mosaic disease symptoms of these progeny and the two parents were surveyed three times, either under natural infection in 11 different environments or after three artificial infections with mixed sugarcane mosaic virus (SCMV) and sorghum mosaic virus (SrMV) inoculum. Analysis of consolidated survey data enabled the identification of 29 immune, 55 highly resistant, 70 moderately resistant, 62 susceptible, and 40 highly susceptible progenies. The disease response data and a high-quality SNP genetic map were used in quantitative trait locus (QTL) mapping. The results showed that the correlation coefficients (0.26~0.91) between mosaic disease resistance and test environments were significant (p < 0.001), and that mosaic disease resistance was a highly heritable quantitative trait (H2 = 0.85). Seven mosaic resistance QTLs were located to the SNP genetic map, each QTL accounted for 3.57% ~ 17.10% of the phenotypic variation explained (PVE). Furthermore, 110 pathogen response genes and 69 transcription factors were identified in the QTLs interval. The expression levels of nine genes (Soffic.07G0015370-1P, Soffic.09G0015410-2T, Soffic.09G0016460-1T, Soffic.09G0016460-1P, Soffic.09G0017080-3C, Soffic.09G0018730-3P, Soffic.09G0018730-3C, Soffic.09G0019920-3C and Soffic.03G0019710-2C) were significantly different between resistant and susceptible progenies, indicating their key roles in sugarcane resistance to SCMV and SrMV infection. The seven QTLs and nine genes can provide a certain scientific reference to help sugarcane breeders develop varieties resistant to mosaic diseases.